From Hollywood Mobster to Russian Gangster: Representations of Mafia in Coppola’s Godfather Trilogy and Balabanov’s Brother Films - Lara Hania Olszowska (Slovo, 2022)
This study examines the changed mythology of crime in the Hollywood gangster genre resulting from new representations of mafia in Francis Ford Coppola’s Godfather trilogy. The trilogy will be viewed as a point of departure for new experimentations in the gangster genre in response to the Russian experience of mafia, namely in Aleksei Balabanov’s Brother film sequence. This analysis will discuss the key themes that appear in Coppola’s trilogy including family, masculinity, morality, and identity and consider the extent to which they either translate to or mutate in Balabanov’s sequence. This research will also explore how Balabanov infuses his films with unique Russian stylistic elements from the bylina (fairy-tale) and aesthetics from chernukha (dark cinema) in order to create a reimagined version of the gangster film. This consideration of the filmic depictions of mafia does not attempt to define the mafia in its truly existing form but seeks to understand how two different experiences of mafia and their interpretations can compare on screen, and how this reveals the tension between resisting and accepting the influence of Hollywood and America on Russian cinema and society.
Keywords: gangster genre; mafia film; gangster hero; The Godfather; family; brotherhood; morality; masculinity; Russian cinema; Russian national identity; Italian American identity; social critique